Governing Abortion By Standards. Abortion Policies In Brazil Since The Late 1980s - Matthieu de Castelbajac (e-cadernos ces, 2009)
Brazil is one of the few countries with restrictive abortion laws to have implemented specialized hospital services to attend patients eligible for non-criminal abortion. Studying the regulation process which accompanied the implementation of these services from the late 1980s onward, the present article describes the emergence of a “government by standards” applied to legal as well as clandestine situations of abortion.